MODEL HUBUNGAN ANTARA VOLUME LALULINTAS DENGAN TARIF JALAN TOL - Prasetyanto, Dwi; Akmalah, Emma (Jurnal Transportasi, 2013)
Indonesia has experienced increasing economic growth every year. This recent trend needs to be supported by adequate transportation infrastructures, especially roads. Since there is limited budget for infrastructure development, the government has invited private investors for toll road construction. Toll tariff and traffic volume are two main factors that affect toll road income and investment. A method based on financial approach needs to be developed to enhance the benefit cost analysis of toll road construction and furthermore to determine the toll tariff. Factors that affect toll tariff were analyzed based on vehicle number and vehicle growth rate. The elasticity theory was applied in this case study to identify the effects of toll tariff on traffic volume. A model of critical traffic volume was created based on the analysis of several factors such as construction cost, operation and maintenance cost, payback period, and internal rate of return. The results from Jia method and the Present Worth Factor (PWF) method show that the relationship between traffic volume and toll tariff is very sensitive, indicated by the elasticity value equal to 1. The difference between the two method is about 27% and is caused by the double counting on taxes on Jia method.Â